2011
DOI: 10.1055/s-0031-1296598
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Imidafenacin (KRP-197/ONO-8025), a New Bladder Selective Anti-cholinergic Agent, in Rats

Abstract: Imidafenacin (CAS 170105-16-5, KRP-197, ONO-8025) has been developed for the treatment of overactive bladder as a new anti-cholinergic with high affinities for muscarinic acetylcholine M3 and M1 receptors. The pharmacological profiles of imidafenacin on the urinary bladder function by determining carbamylcholine (CCh)-induced decrease in bladder capacity and distention-induced rhythmic bladder contraction in conscious rats were investigated. In addition, effects of imidafenacin on CCh-induced salivary secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Imidafenacin also occupied muscarinic receptors to some extent, but did not induce cognitive impairment at all. This is consistent with pharmacological data showing that imidafenacin does not affect escape latency in the Morris water maze task in rats (spatial learning and memory) [65] and with clinical data showing that this agent is well-tolerated with fewer adverse effects [66-69]. Both imidafenacin and darifenacin have moderate polarity and low lipophilicity, suggestive of lower permeability.…”
Section: Brain Muscarinic Receptor Binding Evaluated By Positron Emissupporting
confidence: 87%
“…Imidafenacin also occupied muscarinic receptors to some extent, but did not induce cognitive impairment at all. This is consistent with pharmacological data showing that imidafenacin does not affect escape latency in the Morris water maze task in rats (spatial learning and memory) [65] and with clinical data showing that this agent is well-tolerated with fewer adverse effects [66-69]. Both imidafenacin and darifenacin have moderate polarity and low lipophilicity, suggestive of lower permeability.…”
Section: Brain Muscarinic Receptor Binding Evaluated By Positron Emissupporting
confidence: 87%
“…In vitro research has shown that imidafenacin inhibits rat and human urinary bladder smooth muscle contraction by mediating antagonism of the M 3 muscarinic receptor subtype and regulating acetylcholine release by mediating the prejunctional facilitatory M 1 subtype 8,12. In addition, because imidafenacin has the highest relative potency (8.8), calculated as the ID 50 of salivary secretion divided by the ID 30 of distention-induced rhythmic bladder contraction in conscious rats, among propiverine (0.9), tolterodine (5.0), oxybutynin (1.4), and darifenacin (1.4), the drug has organ selectivity for the bladder over the salivary gland 9. Yamazaki et al reported that the relative bladder selectivity of imidafenacin, solifenacin, and tolterodine was 15-fold, 1.7-fold, and, 2.5-fold higher than for the salivary gland; 150-fold, 1.9-fold, and 9.2-fold higher than for the colon; and 50-fold, 12-fold, and 4.6-fold higher than for the heart, respectively, compared with propiverine in a rat study 13.…”
Section: Pharmacological Characteristics Of Imidafenacinmentioning
confidence: 99%
“…Imidafenacin, which was developed by Kyorin Pharmaceutical Company (Tokyo, Japan) is an antimuscarinic agent used to treat OAB and has high affinity for the M 3 and M 1 muscarinic receptor subtypes and low affinity for the M 2 subtype 8,9. In addition, it shows organ selectivity for the bladder over the salivary glands.…”
Section: Introductionmentioning
confidence: 99%
“…It has selectivity for M3 and M1 receptors over M2 receptor and apparent functional selectivity for the bladder [10]. In a phase 3 trial in Japan [11], the efficacy and tolerability of imidafenacin (0.1 mg twice daily) was compared to placebo and propiverine (20 mg once daily) in 781 patients with OAB.…”
Section: Introductionmentioning
confidence: 99%